(untitled) - Leong, Tan Cheng (Singapore, 1993)
Covers the dosmetic market, foreign investment in Vietnam; the Vietnam business system; real life, business culture and etiquette ...
Keywords: Investments, foreign,Đầu tư, nước ngoài